Impact of the Zn–Co content on structural and magnetic characteristics of the Ni spinel ferrites. Issue 13 (1st July 2022) - Vinnik, D.A.; Sherstyuk, D.P.; Zhivulin, V.E.; Zhivulin, D.E.; Starikov, A.Yu.; Gudkova, S.A.; Zherebtsov, D.A.; Pankratov, D.A.; Alekhina, Yu.A.; Perov, N.S.; Trukhanov, S.V.; Trukhanova, E.L.; et al.
Abstract: The manuscript describes the impact of the chemical composition (Co 2+ /Zn 2+ ions content), crystal and magnetic characteristics of substituted Ni0.3 Zn0.7-x Cox Fe2 O4 (0≤x ≤ 0.7) Ni-based spinels (or NZCF). The initial NZCF powders were prepared using the classic ceramics method. All investigated samples were characterized by a single-phase state with a spinel-like structure – SG: Fd-3m. The average chemical composition of the final NZCF powders correlated well with the initial stoichiometry. After XRD data refinement, we observed a linear decrease of the lattice parameters and volume of the unit cell from a = 8.4085 Å till a = 8.3689 Å and from V = 594.51 Å 3 till V = 586.14 Å 3 with x increasing from 0 to 0.7, respectively. It was explained by the smaller ionic radius of Co 2+ compared to Zn 2+ . A strong impact of the Co 2+ /Zn 2+ ratio in Ni0.3 Zn0.7-x Cox Fe2 O4 (0≤x ≤ 0.7) Ni-based spinels on their magnetic characteristics was demonstrated. An increase in Co 2+ content from x = 0.0 to x = 0.7 leads to an increase in the remnant magnetization Mr and coercivity Hc with non-linear changes in magnetization saturation Ms . It can be explained by the competition of two factors: i. Larger magnetic moment of the Co 2+ ion in comparison with the Zn 2+ ; and ii. The features of the substituent distribution in the spinel matrix. It was observed that anisotropic parameters curves are not rectilinear. This behavior has been explained by the disproportionate contribution of two competing effects, namely, an increase in the f stiffness of the Ni 3+ (Zn 2+, Co 2+/3+, Fe 3+/4+ ) –O 2- - Fe 3+/4+ (Ni 3+, Zn 2+, Co 2+/3+ ) indirect superexchange interactions and an increase in the Ms saturation magnetization with an increase in the x concentration of the Co 2+/3+ cations.